The Frontiersman: A Tale of the Yukon - Cody, H. A. (Hiram Alfred), 1872-1948 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Frontiersman: A Tale of the Yukon" by H. A. Cody is a novel written in the early 20th century. This adventurous tale centers on Keith Steadman, a hardy northman and trailsman, as he navigates the treacherous wilderness of the Yukon, facing both the harsh elements and the wild creatures that inhabit it. Throughout his journey, he encounters characters grappling with desperation, survival, and moral dilemmas that test their humanity. The opening of the story introduces us to Keith Steadman, as he trudges through a snow-covered landscape in search of a destination called Klassan. The seemingly serene setting quickly turns dangerous when he becomes aware of a lurking wolf and discovers a distressed dog that leads him to a cryptic plea for help. This mysterious encounter sets off a chain of events where Keith, despite being in dire straits himself, chooses to help a stranger in need. As the narrative progresses, Keith$1 (Bs character is revealed to be marked by compassion and bravery, establishing a foundation for the challenges and conflicts he will face in the unforgiving wilderness and amongst complex human interactions. (This is an automatically generated summary.)s
Release date is 2010-03-26
Produced by Al Haines
Keywords: Yukon River Valley (Yukon and Alaska) -- Fiction